Lexical Search and Retrieval in Aphasia: A Computational Analysis of Semantic Fluency. - Hambric, Channing E.; Middleton, Erica L.; Kumar, Abhilasha A. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Effectively searching among related items in memory is a hallmark of neurotypical cognition, and analyses of retrieval patterns in the semantic fluency task have provided invaluable insight into how individuals navigate an interconnected conceptual–lexical network. However, few studies have assessed retrieval patterns in the semantic fluency task among people with aphasia (PWA). Method: In the present work, we used computational modeling to investigate the types of lexical information healthy controls (n = 47) and PWA (n = 53) use during semantic memory search. We also assessed how these metrics related to other aphasia battery measures, including tests probing different aspects of semantic processing. Results: Compared to neurotypical controls, PWA produced fewer items, and consecutive items were less phonologically similar. Computational modeling of search behavior indicated that, whereas controls primarily used phonology to search within local clusters of related items, PWA were influenced by phonology both within clusters and at switch points. We also found that verbal semantic comprehension (measured via synonymy triplet scores) was negatively associated with average consecutive phonological similarity in the semantic fluency task, suggesting that PWA with impaired conceptual–lexical access may be more likely to exploit phonological similarity as a compensatory measure. Conclusion: Altogether, the results indicate that individuals with aphasia struggle with adapting search cues during the semantic fluency task compared to neurotypical speakers, and the present work showcases the utility of the computational modeling approach for characterizing semantic memory search in neurotypical and language-impaired populations.